Optimization of the prostaglandin F2α receptor for structural biology - Marine Salze; Sébastien Chrétien; Tegvir S. Boora; Madalina Macovei; Eric Barbeau; Véronique Blais; Stéphane A. Laporte; Martin Audet (PLoS ONE, 2025)
Prostaglandin F2ɑ (PGF2ɑ) is a bioactive lipid derived from arachidonic acid and is involved in many physiological and pathophysiological processes, such as parturition, vascular tone regulation, glaucoma and inflammation. It acts by binding to the Prostaglandin F2ɑ receptor (FP), a G Protein-Coupled Receptor (GPCR) that mediates signaling events by engaging intracellular heterotrimeric G protein effectors. The orthosteric binding site of lipid-binding receptors displays greater efficacy-dependent plasticity that hinders the design of ligands. Solving the structure of FP with ligands of different efficacies at an atomic level is important to fully understand its mechanism of activation and inhibition. Most purified FP-ligand complexes are unstable in vitro. The development of new X-ray crystallography and single particle cryo-electron microscopy (cryoEM) strategies to understand receptors’ signal transduction requires improved purification yield and in vitro stability of the receptor. Here, we present a protein engineering effort to optimize the FP protein sequence for use in structural biology. Strategies involve protein insertion sites in the third intracellular loop (ICL3), N-terminal and C-terminal deletions, and single-point mutations that favorably affect receptor purification yield and stability in vitro. The best FP construct displays a yield of 1.5 mg/L and a stability of 59oC, which constitute a threefold improvement in purification yield and 9oC increase in stability over the wild-type receptor. These modifications in the receptor are suitable for pursuing alternative strategies for improving FP purification yield and for studying FP binding efficacy to its ligands through structural biology approaches.